(untitled) (Dhaka University Law Journal, 2025)
This study was conducted among the experts having good knowledge of the competition law and experience of dealing with the Competition Commission of Bangladesh. This first-of-its-kind study found certain interesting needs to be fulfilled for the better functioning of the Commission and the Competition Act 2012 in Bangladesh. Certain phenomena were reported as common flaws requiring attention by the respondents and they are: manpower, financial issues/ budget, logistics, and ambiguity/‘lack of precision’ of the law. Some unique flaws were identified by rather a minority number of the respondents but deserve attention: Appeal issues/authority, overlapping of power, enforcement hurdles, independence, motivation and bureaucracy, and ‘lacking in sector specific experts’. Furthermore, companies holding ‘significant market power position’ could be a concern for the Regulators. The respondent supported that the Commission should get involved in price-controlling of essential medicine to foster access to healthcare. Respondent underscored the importance of the ‘drug control law and drug policy’ in Bangladesh context, to control the rising cost of medicine. The respondents viewed the Act and the Commission from ‘unsuccessful’ to ‘partially successful’ and ‘successful’; therefore, mixed and varied responses were observed. Multiple respondents recommended the amendment of the Act, including the Appeal provision. Dhaka University Law Journal, 2024, 35 (1), 53-86